Therapeutic Communication Theraphy to Improving Social Interaction of Autism Children (Case Study in SLB Negeri Autis Medan) - Amanda, Tami Gustia; Pohan, Syafruddin; Mazdalifah, Mazdalifah (Budapest International Research and Critics University, 2021)
The purpose of this study was to analyze the application of therapeutic communication therapists in increasing social interaction of children with autism in SLB Negeri Autis Medan. The research method used is a case study method with a qualitative approach. The research subjects were 3 (three) therapists at SLB Negeri Autis Medan and 2 (two) triangulation informants, they are parents of autistic children who school in SLB Negeri Autis Medan and one as psychologist. Data collection techniques using in-depth interviews and the theory used as a reference in this research is the theory of relationship building in therapeutic communication which is derived from interpersonal communication theories. The research findings after the data is saturated and fulfiiled show that the application of therapeutic communication therapy in increasing social interaction of children with autism is by using the ABA method and through the stages of assessment, observation, self-introduction and environment and classical class. The findings also indicate that there are supporting factors as well as inhibiting factors for the application of therapeutic communication therapy, namely acceptance and parental participation, therapeutic methods, therapeutic media, the ability of therapists, the severity of children with autism and dietary food. The researcher concluded that the application of therapeutic communication therapy in increasing the social interaction of children with autism in SLB Negeri Autis Medan using the ABA method and through four (4) stages was appropriate in increasing social interaction and communication of children with autism in the school environment.